Penerapan Terapi Pijat Pada Pasien yang Menjalani Hemodialisa: A Scoping Review - Hasniatisari Harun; Yusshy Kurnia Herliani; Sri Hartati Pratiwi; Anita Setyawati (Malahayati Nursing Journal, 2025)
ABSTRACT The prevalence of chronic kidney failure in the world is increasing every year. Most patients require hemodialysis as a kidney replacement therapy. Complementary and alternative medicine (CAM) researchers revealed that massage therapy is widely used by hemodialysis patients to overcome the side effects caused by hemodialysis. To identify the effectiveness of massage therapy in hemodialysis patients. This scoping review was developed based on the Arskey and O'Malley framework. Study searches were conducted through Scopus and CINAHL. Inclusion criteria in selecting articles included: primary research results discussing the application of massage therapy in patients undergoing hemodialysis in the form of full-text articles, in English, and published in 2019-2023. The 13 articles analyzed in this study revealed that massage therapy has a positive effect on general health, physical symptoms, nausea, fatigue, pain due to muscle cramps, and restless legs syndrome (RLS), pruritus severity, sleep quality, insomnia severity, quality of life, anxiety, and intradialytic hypertension in hemodialysis patients. Foot massage therapy can be used as a complementary therapy to reduce the side effects of hemodialysis. Nurses and health workers need to have certified massage therapy skills in order to provide and teach massage to hemodialysis patients and their families. Keywords: Hemodialysis, Massage Therapy, Nurses.  ABSTRAK Prevalensi penyakit gagal ginjal kronis di dunia meningkat setiap tahun. Sebagian besar pasien memerlukan tindakan hemodialisa sebagai terapi pengganti ginjal. Para peneliti complementary and alternative medicine (CAM) mengungkapkan bahwa terapi pijat banyak digunakan oleh pasien hemodialisa untuk mengatasi efek samping yang ditimbulkan oleh hemodialisa. Untuk mengidentifikasi efektivitas terapi pijat pada pasien hemodialisa. Scoping reviewini dikembangkan berdasarkan kerangka kerja Arskey dan O’Malley. Pencarian studi dilakukan melalui Scopus dan CINAHL. Kriteria inklusi dalam pemilihan artikel meliputi: hasil penelitian primer yang membahas tentang penerapan terapi pijat pada pasien yang menjalani hemodialisa dalam bentuk artikel teks lengkap, berbahasa Inggris, dan dipublikasikan ahun 2019-2023. 13 artikel yang dianalisis pada studi ini mengungkapkan bahwa terapi pijat memiliki pengaruh positif terhadap kesehatan umum, gejala fisik, mual, kelelahan, nyeri akibat kram otot, dan restless legs syndrome (RLS), keparahan pruritus, kualitas tidur, keparahan insomnia, kualitas hidup, kecemasan, dan hipertensi intradialitik pada pasien hemodialisa. Terapi pijat kaki dapat dijadikan sebagai terapi komplementer untuk mengurangi efek samping hemodialisa. Perawat dan petugas kesehatan perlu memiliki keterampilan terapi pijat bersertifikasi agar dapat memberikan dan mengajarkan pijat pada pasien hemodialisa dan keluarganya. Kata Kunci: Hemodialisa, Perawat, Terapi Pijat